Job Satisfaction Of Bank Syariah Indonesia Employees Post-Merger - Surya Hendrawan; Nur Hendrasto; Muhammad Fahri Farid; Desmy Riani (JPS (Jurnal Perbankan Syariah), 2023)
This research aims to analyze the influence of rewards, supervision, career development, co-workers, and the nature of work on the job satisfaction of Bank Syariah Indonesia employees. This research uses a quantitative approach with primary data. The population of this research is Bank Syariah Indonesia employees who work at the head office and the network undergoing a merger. The sampling technique used random samples, and the number was determined using Slovin's measurements so that 354 respondents were obtained. The data collection technique uses a questionnaire with a Likert scale. Data analysis uses a structural equation model with the help of SmartPLS 3 software. This research shows that rewards, supervision, career development, co-workers, and the nature of work positively and significantly affect the job satisfaction of Bank Syariah Indonesia employees after the merger. Theoretical research results complement existing theory and can be a reference for merging companies regarding management programs to increase employee performance satisfaction.